Tetrahydrobiopterin: a vascular redox target to improve endothelial function. - Channon, K (2012)
Loss of normal endothelial function and bioactivity of nitric oxide (NO), associated with increased production of reactive oxygen species (ROS), are characteristics of cardiovascular disease states. There is good experimental evidence that these abnormalities are causally related to cardiovascular disease pathogeneses, and are amenable to therapeutic intervention. However, simple attempts to increase NO levels or reduce "oxidative stress", for example using nonselective anti-oxidant drugs, have shown no benefit as treatments of cardiovascular disease. Increasing evidence highlights the need to better understand NO and ROS mediated signaling mechanisms in endothelial function, in order to identify more rational and selective therapeutic targets. The NO synthase co-factor, tetrahydrobiopterin (BH4) is a redox active molecule which regulates NO and ROS production by NO synthase and provides an exemplar of redox dependent signaling in the endothelium, with relevance to cardiovascular disease. Loss of endothelial cell BH4 is observed in cardiovascular disease states and results in loss of NO, but increased ROS production by endothelial NO synthase. Genetic mouse models of augmented endothelial cell BH4 synthesis have shown proof of concept that endothelial cell BH4 can alter cardiovascular disease pathogenesis, but clinical trials of BH4 therapy in vascular disease have been limited by systemic oxidation and limited endothelial cell uptake of BH4. In contrast, some existing therapies such as statins appear to exert favourable effects on endothelial cell BH4 and endothelial NO synthase function. Identifying specific redox mechanisms and targets in the endothelium will provide new potential targets for future drug treatments.